The Role of Exosomes as Mediators of Neuroinflammation in the Pathogenesis and Treatment of Alzheimer’s Disease - Weng, Shiting; Lai, Qi-Lun; Wang, Junjun; Zhuang, Liying; Cheng, Lin; Mo, Yejia; Liu, Lu; Zhao, Zexian; Zhang, Ying; Qiao, Song (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a common neurodegenerative disease characterized by progressive dementia. Accumulation of β–amyloid peptide 1–42 and phosphorylation of tau protein in the brain are the two main pathological features of AD. However, comprehensive studies have shown that neuroinflammation also plays a crucial role in the pathogenesis of AD. Neuroinflammation is associated with neuronal death and abnormal protein aggregation and promotes the pathological process of β-amyloid peptide 1–42 and tau protein. The inflammatory components associated with AD include glial cells, complement system, cytokines and chemokines. In recent years, some researchers have focused on exosomes, a type of membrane nano vesicles. Exosomes can transport proteins, lipids, microRNAs and other signaling molecules to participate in a variety of signaling pathways for signal transmission or immune response, affecting the activity of target cells and participating in important pathophysiological processes. Therefore, exosomes play an essential role in intercellular communication and may mediate neuroinflammation to promote the development of AD. This paper reviews the occurrence and development of neuroinflammation and exosomes in AD, providing a deeper understanding of the pathogenesis of AD. Furthermore, the role of exosomes in the pathogenesis and treatment of AD is further described, demonstrating their potential as therapeutic targets for neuroinflammation and AD in the future.